Factors Related to Behavior of Using Personal Protective Equipment on Filling Lithos Workers - Siregar Reymond Sahala Pangihutan (The Indonesian Journal of Occupational Safety and Health, 2019)
Introduction: Every workplace has risks and risks to the safety and health of workers. Personal Protective Equipment (PPE) as the last control or last effort to control risk in workplace. Using personal protective equipment is influenced by a person's behavior which consists of three factors namely predisposing factors, enabling factors and driving factors. The purpose of this study was to analyze factors related to the behavior of using PPE on workers in the filling lithos process PT. Pertamina Lubricants Production Unit Gresik. Metods: This study was an observational analytic study, using a cross sectional research design. The research sample was 41 people, taken randomly using simple random sampling. Data collection includes age, education, years of service, knowledge, motivational attitudes of PPE availability, supervision and regulations regarding PPE. The data analysis used in this study is Spearman's correlation. Results: Showed that there was a relationship between age factors (p = 0.004) and the behavior of PPE use while other factors were knowledge (p = 0.338), motivation (p = 0.137), availability of PPE, regulations on PPE (p = 0.624) with no association behavior of using PPE. Most samples behave disobediently using PPE. Conclusion:Age has a relationship with my personal use of personal protective equipment and most of the workers behave disobedient using personal protective equipment.  Keywords: behavior, filling lithos workers, personal protective equipment